Neoliberalism and Scientific Research: Exploratory Study in a Portuguese Psychology Center - Araújo, Hugo; Gonçalves, Carlos (Pensando Psicología, 2020)
The present study explores the relationship between the neoliberal paradigm – effectively seen in the Universities’ new public management (NPM) – and the psychologization phenomena, with the intent to raise the scientific and general communities’ awareness about the growing instrumentalization of Psychology and knowledge’s commodification, particularly in scientific research. Thus, we explored the functioning dynamics of a portuguese psychology center, interviewing twelve researchers and understanding the data through a thematic content analysis. This analysis allowed us to have a glimpse of how the neoliberal ideology enters the scientific research exalting the technocratic and efficient criteria, promoting psychologizing discourses that, in their turn, increasingly occupy the public arena. Furthermore, this pioneer exploration in portuguese context helped us realize that, although there’s a clear investment in research diversity, for both theory and methodology, there’s also a preference for anglo-american psychology.
Keywords: free market; neoliberalism; scientific research; management policies